An analytical study of some Bio-Kinematic variables in the stage of kicking the ball and the mechanism of controlling it when scoring to the goal from different situations of indoor Futsal - Jawad , Wael Kassim; Daikh, Yarub Abdul Baki; Ward, Karrar Fahem (International Journal of Psychosocial Rehabilitation, 2020)
Scoring skill is of great importance mechanically, taking into account a lot of physical abilities and biochemical variables in order to achieve successful scoring in terms of changes that occur in the corners of the body parts when different scoring positions according to situations preceding this situation, For example, is the scoring position the same when performing scoring from the side handling with the scoring mode of rolling ball and movement? And what differences occur because of those cases. As well as researchers tried to find solutions and provide information on those cases and conditions to reach this skill to high performance, The aim of the study is to identify the values of some biochemical variables in the ball kicking and the mechanism of control when scoring on goal from different situations, as well as to identify the differences in the values of those variables in the research sample, As for the study methodology, the researchers chose the descriptive method in the survey method , In addition, the sample of the study was selected from some of the players of the futsal for the excellent degree, representing the clubs of the municipality and the south oil . as well as conducted the exploratory and main experiment and then the data extracted was processed by appropriate statistical means, and the results were presented and discussed, where the researchers reached a set of conclusions, including that it turns out that the players are working to increase the fold in The knee joint of the anchor leg in the moment of kicking the ball in the case of scoring from the side roll more than in the cases of scoring from the rolling or of handling, as well as showing that the players are working to increase the angle of the hip joint in the moment of kicking the ball in the case of scoring from handling more than in the case of scoring from the rolling back and the scoring from the side roll.